(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The paper analyses both the importance of introducing Industry 4.0-related courses into the curricula of Industrial Engineering and Management (IEM) education and the appropriate ways to do so. The case study focuses on questioning two categories of relevant stakeholders: students and professors. It also analyses their position on the introduction of new courses tailored to Industry 4.0 content and/or the integration of Industry 4.0 elements into existing courses.